Integrasi Teknologi dalam Pembelajaran IPS melalui Pendekatan Deep Learning di SMP Negeri 7 Makassar - Ahmad Nur; Alimin Alwi; Najamuddin (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the implementation of Social Studies (IPS) learning based on a deep learning approach through the integration of educational technology at SMP Negeri 7 Makassar and its impact on the quality of learning. The research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of the deep learning approach improved students’ participation, deeper conceptual understanding, and critical thinking skills in analyzing social phenomena. The integration of educational technology through interactive digital media, learning videos, and online platforms also enhanced students’ learning interest, digital literacy, and understanding of abstract materials. Despite challenges related to limited facilities and technological readiness, Social Studies learning based on deep learning through the integration of educational technology proved effective in improving the quality of learning